Innovative molecular design for a volume oriented component diagnostic: Modified magnetic nanoparticles on high performance yarns for smart textiles - Bartusch, Matthias; Hetti, Mimi; Pospiech, Doris; Riedel, Maria; Meyer, Joerg; Toher, Cormac; Neu, Volker; Gazuz, Igor; Shagolsem, Lenin S.; Sommer, Jens-Uwe; Hund, Rolf-Dieter; Cherif, Chokri; et al. (Advanced Engineering Materials, 2014)
A novel way for destruction-free, volume-oriented component diagnostics is reported. Surface-modified magnetic nanoparticles are applied for impregnation of plasmaactivated UHMW PE textiles, which are embedded into an epoxy matrix. Supported by simulations, this comprehensive study from single molecules to composites extends the knowledge of molecular interactions at polymer interfaces and broadens the application of nondestructive methods.
CRIS-Team Scopus Importer:2023-03-20